Respuesta :

Answer: 125

Step-by-step explanation:

First, solve for x in the first equation.

1) Subtract 1 from both sides.

2x = 4

2) Divide by 2 on both sides.

x = 2

Next, substitute the value of x into the second expression.

(2 + 3)^3

= 5^3

= 125

Answer:

The value of (x + 3)³ is 125.

Step-by-step explanation:

First, we have to find the value of x.

To do so, start with the first equation, 2x + 1 = 5.

We can easily solve this equation to find the value of x.

First, start by subtracting 1 from each side.

This leaves us with 2x = 4.

Next, divide by two on each side.

This will leave us with the answer x = 2.

Now we know the value of x = 2.

All that's left to do is substitute the value of x, 2, for x.

First, start with the second equation (x + 3)³.

We know that x is equal to 2, so we can enter 2 for x.

We then have the equation (2 + 3)³.

Next, solve.

Add the 2 and the 3 together.

Now, the equation is 5³.

5³ is equal to 5 · 5 · 5

5 · 5 · 5 = 125

To sum up,

We found out that x = 2

Using 2 for x, we found out that (x + 3)³ is equal to 125.